2017
DOI: 10.1016/j.beth.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Clinical Research Using Factorial Designs: A Primer

Abstract: Factorial experiments have rarely been used in the development or evaluation of clinical interventions. However, factorial designs offer advantages over randomized controlled trial designs, the latter being much more frequently used in such research. Factorial designs are highly efficient (permitting evaluation of multiple intervention components with good statistical power) and present the opportunity to detect interactions amongst intervention components. Such advantages have led methodologists to advocate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…It is unclear why receipt of both components suppressed quit attempts. An advantage of the factorial experiment is that it can reveal such interactions; the causes of such interactions remain unclear (Baker, 2017;Baker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why receipt of both components suppressed quit attempts. An advantage of the factorial experiment is that it can reveal such interactions; the causes of such interactions remain unclear (Baker, 2017;Baker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, future studies could benefit by comparing the outcomes reported in truly RCT, cluster RCTs and factorial designs, as they are feasible to use on larger sample sizes [ 47 ]. While cluster RCTs have been reported to have more potential to detect treatment effects in the most affected groups within the clusters [ 48 , 49 ], the risk of bias in such studies should be detailed, exploring the differences in outcomes reported. Furthermore, each type of STH species is likely to react to nutritional supplements in distinctive ways.…”
Section: Discussionmentioning
confidence: 99%
“…We propose the use of factorial and fractional factorial designs as an alternative methodological approach to standard comparative RCTs and component designs, which has advantages over both for resolving the active components of psychotherapy. Factorial experiments allow one to explore main effects of factors and interactions among factors (23)(24)(25)(26)(27).…”
Section: The Factorial Approachmentioning
confidence: 99%